Association of rs556621 Polymorphism with Development of Stroke in Patients with Cardiovascular Pathology - S. Yu. Nikulina; V. A. Shulman; A. A. Chernova; S. V. Prokopenko; D. A. Nikulin; I. M. Platunova; S. S. Tretyakova; V. N. Maksimov; A. A. Gurazheva (Столичная издательская компания, 2019)
Aim. To study the association of single nucleotide polymorphism rs556621 (G> T) with development of stroke in patients of the East Siberian population with cardiovascular pathology and risk factors.Material and methods. The study involved 260 patients (157 men and 103 women) with stroke (mean age 57.0 [51.0-62.0]) and 272 patients (170 men and 102 women) of the control group (mean age 55.0 [51.0-62.0]). The examination of the main group included: collection of complaints, anamnesis, clinical examination, computed tomography of the brain, electrocardiography, echocardioscopy, ultrasound duplex scanning of extracranial brachiocephalic arteries, daily blood pressure and heart rate monitoring, analysis of the blood coagulation system. The patients of the main group have arterial hypertension, paroxysmal supraventricular tachycardias, dyslipidemia, atherosclerosis of the brachiocephalic arteries, disorders of the hemostatic system. The control group was studied in the framework of the HAPIEE international project. Molecular genetic research was performed by real-time polymerase chain reaction.Results. There were no statistically significant differences in the frequencies of genotypes and single nucleotide polymorphism rs556621 alleles (G>T) in the subgroup of patients with stroke and those in the control group. The frequency of the rare TT genotype among patients with stroke was 13.3%±4.16, among healthy individuals - 8.8±3.37% (p=0.1). Gender differences when comparing the frequencies of genotypes and alleles were also not detected (p>0.05). The frequencies of the TT genotype were approximately the same in the subgroup of patients with arterial hypertension (13.1%±4.22) and in the control group (7.4±5.25%; p>0.05). No significant differences were observed in the frequencies of the rare genotype of the studied polymorphism in the subgroup of patients with supraventricular tachycardias (20.0±14.37%), hypercoagulability (15.9±7.64%) and the control group (8.8±3.37%), p>0.05. A statistically significant relationship was found between the rare genotype TT of single nucleotide polymorphism rs556621 (G>T) and the development of stroke in patients with dyslipidemia and atherosclerotic lesions of the coronary arteries (p=0.041; odds ratio 1.86, 95% confidence interval 1.02-3.41).Conclusion. The genotype of TTs of single nucleotide polymorphism rs556621 (G> T) increases the risk of developing stroke in patients with dyslipidemia and atherosclerosis of the brachiocephalic arteries compared with carriers of the GG and GT genotypes. The obtained data are recommended to be considered when prescribing lipid-lowering and antithrombotic therapy.